Calculation of temperature distribution and rheological properties of the lithosphere along transect II in the Western Carpathian-Pannonian Basin region - DÉREROVÁ, Jana; BIELIK, Miroslav; PAŠIAKOVÁ, Mariana; KOHÚT, Igor; HLAVŇOVÁ, Petra (Contributions to Geophysics and Geodesy, 2014)
The temperature model of the lithosphere along transect II passing throughthe Western Carpathians and the Pannonian Basin has been calculated using 2D integratedgeophysical modelling methodology. Based on the extrapolation of failure criteria,lithology and calculated temperature distribution, we derived the rheology model of thelithosphere in the area. Our results indicate a decrease of the lithospheric strength fromthe European platform and the Western Carpathians towards the Pannonian Basin. Thelargest strength can be observed within the upper crust which suggests rigid deformationin this part of the lithosphere. In the lithospheric mantle, strength almost disappearswhich allows us to assume that the ductile deformation dominates in this part of thelithosphere.